Cluster Analysis of Small Enterprises According to a Risk of Business. - Dissayarungkun, Pinyada (Journal of Applied Statistics and Information Technology, 2021)
The research objectives are to cluster analysis of small enterprises according to the business risk level and study the characteristics of entrepreneurs in each group. The online questionnaire survey with a total of 432 entrepreneurs was used as the data collecting method. The entrepreneurs are divided into 3 groups by K-Means Clustering Analysis. The first cluster namely “Risk of Strategic” is an entrepreneur who has just started a business. Factors that make business decisions because incomes are insufficient. The second cluster namely “Risk of Communication” is an entrepreneur have been in business for 3 - 10 years. Factors that make business decisions because they do not want to work full time / want to be a business owner. The third cluster namely “Risk of Legal” is an entrepreneur that operates businesses for 10 years or more. Factors that make business decisions because it is a family business.